1978
DOI: 10.1159/000128007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motility and Luminal Distension on Dog Small Intestine Hemodynamics

Abstract: The effects of spontaneous intestinal motor activity and artificial luminal distension on mesenteric hemodynamics were studied on isolated canine jejunal loops perfused at normothermia under pulsatile flow with heparinized and oxygenated dogs whole blood. To each increase in intestinal tonic activity or intraluminal distension there is a corresponding linear increase in arterial pressure (under constant flow). The hemodynamic effect of distension is less potent than that produced by spontaneous motility. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The failure of distension to reduce oxygen consumption was attributed to higher resting blood flow in the denervated gut. In the constant-flow preparation, distension to lumen pressures of below 25 mmHg (the level similar to that of the previous study) did not significantly alter intestinal oxygen consumption (109). These findings seem to indicate that the decreased oxygen consumption observed in the innervated gut (121) is secondary to distension-induced decrease in blood flow.…”
Section: Oxygen Consumption Capillary Filtration Coefficient and Lysupporting
confidence: 84%
See 2 more Smart Citations
“…The failure of distension to reduce oxygen consumption was attributed to higher resting blood flow in the denervated gut. In the constant-flow preparation, distension to lumen pressures of below 25 mmHg (the level similar to that of the previous study) did not significantly alter intestinal oxygen consumption (109). These findings seem to indicate that the decreased oxygen consumption observed in the innervated gut (121) is secondary to distension-induced decrease in blood flow.…”
Section: Oxygen Consumption Capillary Filtration Coefficient and Lysupporting
confidence: 84%
“…The effect of luminal distension in decreasing blood flow is less than that of the contraction for the same increment in lumen pressure (16, 1.09). Kachelhoffer et al (109) have shown that for each 1-mmHg rise in lumen pressure, the rise in vascular resistance produced by sustained spontaneous tonic contractions was 1.61 times that produced by luminal distension. There are other reasons for the more limited effect of luminal distension in decreasing total intestinal blood flow.…”
Section: Effects Of Intestinal Luminal Distensionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies 1 –5 have investigated the relationship between individual contractions of the small intestine and blood flow. These studies were done mostly on anaesthetized animals using intact or isolated segments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GI tract disorders, such as ileus, can cause stagnation of gases and contents as well as dilation of the GI tract. The resulting increase in pressure in the GI tract may impair circulation and cause ischemia in the GI tract [5,9]. Therefore, the decrease in gas levels in breaths that was observed in horses with GI diseases in this study may have been due to impairment of circulation.…”
mentioning
confidence: 74%